Proteomic profile of human sinoatrial and atrioventricular nodes in comparison to working myocardium - Agata Krawczyk-Ożóg; Aneta Stachowicz; Grzegorz Szoniec; Jakub Batko; Kamila Stachyra; Filip Bolechała; Marcin Strona; Paweł P. Wołkow; Zeyuan Yin; Halina Dobrzynski; Mateusz K. Hołda (Scientific Reports)
Abstract The proteomic profile of the human cardiac conduction system: the sinoatrial node (SAN) and atrioventricular node (AVN), remains poorly understood. The aim of the current study is to identify proteomic characteristic of the human SAN and AVN in the comparison to working myocardium of the right atrium (RAM) and right ventricle (RVM). The proteomic analysis was performed on 10 autopsied human heart specimens collected from healthy adults. During the data-independent acquisition proteomics analysis 2752 different proteins were identified in all sample sets. In both nodal tissues (compared to working myocardium), the following pathways were upregulated: regulation of Insulin-like Growth Factor transport and uptake by Insulin-like Growth Factor Binding Proteins, post-translational protein phosphorylation, glutathione metabolism, metabolism of carbohydrates, glycolysis and gluconeogenesis. Other common for nodal tissue pathways were these related to immune system and related to extracellular matrix. The pathways related to cardiac muscle contraction were more abundant in RAM and RVM samples. The current study presents extensive comparative analysis of protein abundance in the human SAN and AVN. Few key differences may be found in the nodal proteome in comparison to working cardiomyocytes, including involvement of immune system and upregulated pathways related to extracellular matrix. The SAN exhibits enrichment in the PPAR signaling and pentose phosphate pathways, as well as prostaglandin synthesis and regulatory proteins, compared to the AVN.